2016
DOI: 10.1097/adm.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Reduction in Pregnant Women With Opioid Use Disorder

Abstract: Objectives Nearly 95% of women with opioid use disorder continue to smoke cigarettes during pregnancy. Despite this prevalence and the well-documented adverse effects of smoking on birth outcomes, cigarette smoking is under-addressed in this population. This study examines factors associated with successful smoking reduction among pregnant women with opioid use disorder and the impact of smoking reduction on maternal and birth outcomes. Methods This study is a secondary data analysis of maternal smoking redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In addition, we relied on documentation in the medical record of alcohol and tobacco use during pregnancy, which in turn relied on maternal report; both exposures are likely under-reported and inconsistently documented in the medical record. Published literature reports that more than 90% of women with opioid use disorder smoke cigarettes during pregnancy, a significantly higher prevalence than the 40% in our cohort, confirming likely under-reporting and/or inconsistent documentation of this variable ( 51 53 ). We were also unable to evaluate the potential influence of genetic and epigenetic factors on development ( 54 ).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, we relied on documentation in the medical record of alcohol and tobacco use during pregnancy, which in turn relied on maternal report; both exposures are likely under-reported and inconsistently documented in the medical record. Published literature reports that more than 90% of women with opioid use disorder smoke cigarettes during pregnancy, a significantly higher prevalence than the 40% in our cohort, confirming likely under-reporting and/or inconsistent documentation of this variable ( 51 53 ). We were also unable to evaluate the potential influence of genetic and epigenetic factors on development ( 54 ).…”
Section: Discussionsupporting
confidence: 66%
“…Although brief intervention and skill training decreased smoking levels [ 72 ], only the study by Tuten et al (2012) focused on smoking reduction among women who are pregnant in treatment with methadone for OUD and the use of financial incentives demonstrated a significant impact [ 72 ]. Active engagement in treatment to reduce smoking, as measured by numbers of collected urinalysis samples and mean days of treatment attendance, appeared to lead to a more successful smoking reduction, but even a 50% reduction in smoking was difficult to attain [ 38 ]. Recent publications indicate new studies are being planned to study interventions to REDUCE tobacco consumption in PPWOUD [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note that the majority of the women in the study were smokers (n = 177 smokers vs. 18 nonsmokers) [37]. Ram et al (2016) reported that women who successfully reduced their cigarette consumption during pregnancy exhibited a nonsignificant decrease in spontaneous abortions, higher infant birth weights, and a nonsignificant reduction in the number of infants being treated for NAS (p-values > 0.05 for all comparisons) [38]. The other papers [39][40][41][42][43][44] reported no neonatal outcomes that were significantly different in infants of mothers being treated with methadone who smoked vs. those who did not smoke (p-values > 0.05).…”
Section: Methadone-exposed Infantsmentioning
confidence: 99%
“…Secondary findings of this study are also noteworthy. More than one in ten current smokers also concurrently used opioids in pregnancy, which may not be unusual in a treatment setting given the high prevalence rates of smoking that have been reported among treatment-seeking individuals with opioid use disorder (Chun et al 2009; Ram et al 2016), but was not anticipated in a prenatal care clinic setting. Additionally prevalence rates of cannabis and opioids use in our sample of pregnant women are higher when compared to recent studies on cannabis and opioid use in pregnancy for other populations (Brown et al 2017; Osmundson et al 2018).…”
Section: Discussionmentioning
confidence: 97%